Arduino Based Smart Irrigation Using Advanced Robot - Dr. R. Gopi; A. Srimathi; S. Sudaroli, S. Sudaroli; R. Gayathri Devi; R. Jayashree (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Global food security is largely dependent on the agriculture sector, and technological developments are becoming necessary to meet the growing need for efficient and sustainable farming methods. This paper presents a revolutionary Agriculture Robot that is intended to improve overall crop productivity and resource usage by streamlining the procedures of water spraying and seed sowing. The Agriculture Robot integrates state-of-the- art technologies, including precision navigation systems, real-time sensors, and automation mechanisms. The robot is equipped with a precise seed dispensing system that ensures optimal seed placement, spacing, and depth, promoting uniform crop germination. Additionally, the robot features an efficient water spraying mechanism, utilizing advanced sensors to assess soil moisture levels and crop health, enabling targeted and judicious irrigation practices. The robot employs advanced algorithms and sensors to precisely sow seeds with optimal spacing and depth, ensuring uniform germination and maximizing crop yield. Real-time soil moisture sensors and crop health monitoring enable the robot to make data-driven decisions for targeted water spraying. This minimizes water wastage while maintaining optimal moisture levels for crop growth. Farmers can remotely monitor and control the Agriculture Robot through a user- friendly interface. This feature enhances flexibility and allows farmers to adapt to changing conditions promptly. By integrating cutting-edge technologies, the Agriculture Robot presented in this paper addresses the challenges of labour- intensive and resource-inefficient traditional farming methods. The implementation of this robot has the potential to revolutionize agriculture by increasing productivity, reducing environmental impact, and contributing to sustainable and precision farming practices.